Definición de la configuración y ciclo del proyecto de carbono para los sistemas de producción de cacao bajo en emisiones en Caquetá y Cesar - Blanco, Javier Tomás; Quintana, Angélica; Garcia, Maria Claudia; Navarrete, Manuela; Borda, Carlos; Vanegas, Martha (2023)
This report details the process of implementing carbon projects, from conception to issuance and marketing of certified units. The approach follows a methodology similar to COLCX and covers several phases, from pre-feasibility and conception to accreditation of the carbon initiative. In the pre-feasibility phase, activities with carbon benefits are identified, and the project is financially assessed. Then, the standard and methodology are selected, and the project idea note is formulated. The second phase focuses on feasibility and design, including budgeting and agreements with farm owners. The third phase involves accreditation, opening accounts in the carbon standard, and contracting a Validation and Verification Body. The fourth phase involves the implementation of planned activities and carbon monitoring. Finally, the fifth phase focuses on ongoing operation and monitoring, with the collection of variables, measurement of plots, and application for issuance of certified units. The report also explores the monitoring required for REDD+ and agroforestry projects, highlighting the characteristics of standard monitoring plans such as COLCX, BCR, and CERCARBONO. In addition, it presents alternative configurations for sustainable cocoa carbon projects, including decisions on geographic scope, unitary or grouped project submission, and specific considerations for REDD+ and agroforestry projects. The choice between submitting a single project for the departments of Cesar and Caqueta or separate projects is based on financial, technical, and institutional capacity factors. The "unitary" or "grouped" configuration of the project is addressed based on the prior definition of areas and agreements with landowners or the possibility of adding new operational units during implementation.